Forum Theatre as a Form of Protest: A Practice-Based Investigation - Chetty, Teakshania (University of the Witwatersrand, Johannesburg, 2024)
This study examines Forum Theatre's (FT) impact within the Fees Must Fall (FMF) movement in South Africa, highlighting its role in protest and social change. Findings show FT empowers participants, promotes understanding of systemic injustices, and fosters solidarity and innovative strategies for activism. The research advocates for further investigation into FT's effects, collaboration between FT practitioners and social movements, and increased support for FT initiatives. Ultimately, FT is presented as a vital tool for social activism, enabling mobilization, education, and empowerment.
A research report Submitted in fulfillment of the requirements for a Master of Arts in the field of Applied Drama: Theatre in Education, Communities and Social Contexts, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Practice-Based Investigation; Forum Theatre; SDG-4: Quality education